2023
DOI: 10.3389/forgp.2023.1229543
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical leadership: a meta-analytical review

Abstract: The past few decades have brought a rapid emergence of research related to paradoxical leadership behavior (PLB), yet extant research remains scattered, inconsistent and somewhat contradictory. This meta-analysis examines the association between PLB and follower/team outcomes, specifically exploring PLBs incremental validity over other established leadership styles, namely transactional, transformational and servant leadership, as well three competing mechanisms through which PLB elicits positive effects. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Numerous studies have confirmed that PL can significantly enhance employees' creativity and inspire them to engage in more innovative behaviors (Lee et al, 2023). At the same time, considerable body of research on leadership also has provided evidence that the actions of leaders have a substantial impact on the behavior of employees, both directly and indirectly by affecting their emotional and cognitive states (Hofstee et al, 2021).…”
Section: The Mediating Role Of Harmonious Work Passionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed that PL can significantly enhance employees' creativity and inspire them to engage in more innovative behaviors (Lee et al, 2023). At the same time, considerable body of research on leadership also has provided evidence that the actions of leaders have a substantial impact on the behavior of employees, both directly and indirectly by affecting their emotional and cognitive states (Hofstee et al, 2021).…”
Section: The Mediating Role Of Harmonious Work Passionmentioning
confidence: 99%
“…Numerous studies have confirmed that PL can significantly enhance employees' creativity and inspire them to engage in more innovative behaviors (Lee et al. , 2023).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%